24 Hours in a Zoo - Cook, Lan; Thomas, Anastasia; Ashton-Booth, Tom (London : Usborne Publishing Limited, 2023)
A lively comic strip exploring the work that goes on behind the scenes in a zoo. Tai is mad about animals and dreams of becoming a zookeeper when he grows up. Today is his chance to access all areas and explore what goes on behind the scenes at a zoo for the day. In this story you'll discover what it's like to handle a giant snake, how the zoo prepares for the arrival of a new animal and what happens when an animal goes missing. See some cutting-edge science in action, and find out how zoos work to protect endangered species, and what they do with all that dung.Written in collaboration with experts at Chester Zoo
Includes index
Keywords: Zoos -- Juvenile literature; Animals -- Juvenile literature; Zoos -- Comic books, strips, etc; Animals -- Comic books, strips, etc; Juvenile works; Graphic novels